The Contribution of SNC Civilization House in Enhancing Generation Alpha’s Understanding of Islamic Cultural History in Rejang Lebong - Ana Maryati; Tri Ulandari (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M) Sekolah Tinggi Agama Islam As-Sunnah, 2026)
Education in Indonesia continues to face challenges in fostering meaningful learning, particularly in Islamic Cultural History (SKI), which requires historical understanding, critical reflection, and value internalization. These challenges intensify for Generation Alpha learners, whose learning preferences are visual, interactive, and technology-mediated. This study examines the contribution of Rumah Peradaban SNC, a non-formal educational institution, to Generation Alpha's understanding of Islamic Cultural History through an experiential learning approach. Using a descriptive qualitative design, data were collected through in-depth interviews, participant observation, and documentation involving facilitators, students, parents, and program administrators, and analyzed through data reduction, display, and conclusion drawing, with credibility ensured via source and method triangulation. Findings show that Rumah Peradaban SNC strengthens students' historical understanding by integrating storytelling, visual media, educational games, role play, collaborative activities, and guided reflection into a coherent learning process. Meaningful historical learning emerges not from technology alone but from the interaction of experiential activities, facilitator guidance, and reflective dialogue that enable students to reconstruct historical narratives and internalize Islamic values. The program nonetheless faces contextual challenges, including unequal digital infrastructure, unstable connectivity, and students' susceptibility to technological distraction, underscoring the need to balance digital engagement with reflection. This study contributes to discussions on Generation Alpha by showing that experiential learning bridges students' digital learning characteristics and the reflective aims of Islamic Cultural History education, and highlights the complementary role of non-formal institutions in strengthening formal Islamic education through contextual, experience-based learning.